PENGARUH PENGGUNAAN AUTOPLAY MEDIA STUDIO DAN FOCUSKY TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SEKOLAH MENENGAH PERTAMA NURUL ISLAM JEMBER - AIN, MUHAMMAD (IJIT: Indonesian Journal of Islamic Teaching, 2018)
Abstract: Success in the learning process becomes important indicators over the accomplished a goal of learning. In this case, the media learning used to attract attention and make students actively in the learning process. Learning media use which has not been fullest making students less motivated in the following learning, so that students can study results are low. Innovation in learning PAI is urgently needed, in order to increase motivation and student learning outcomes. One of the learning media by learning media autoplay media studio and focusky. The purpose of the research are to explain the difference of learning motivation and student learning outcomes between groups using learning media autoplay media studios, groups using focusky media learning and groups using conventional learning on the subjects on Islamic Religious Education Lesson Class VII in Junior High School Nurul Islam Jember. The result of the analysis shows that (1) there are significant differences of students learning motivation between groups using media learning media autoplay media, groups using focusky media and group learning using conventional teaching on Islamic Class VII in Junior High School Islam Jember with value F equal to 3,606 with significance 0,031. (2) there is a significant difference of students' learning outcomes between groups using media learning media autoplay media, group using focusky media and group learning using conventional learning on Islamic Class VII in Islamic Junior High School Nurul Islam Jember with value F of 3,913 with a significance of 0,024. (3) there is a significant difference of learning motivation and student learning outcomes between group using media of learning media autoplay media, group using focusky media and group learning using conventional learning in the subject on Islamic Class VII in Junior High School Nurul Islam Jember for Pillae Trace (sig. 0.010), Wilk Lambda (sig. 0.008), Hotelling Trace (sig. 0,007), Roy's Largest Root (sig. 0.001). That is for Pillae Trace, Wilk Lambda, Hotelling Trace, Roy's Largest Root are all significant. Abstrak: Penilaian merupakan suatu bagian penting dalam proses pembelajaran Keberhasilan dalam proses pembelajaran menjadi indikator penting atas tercapainya suatu tujuan pembelajaran. Dalam hal ini, media pembelajaran digunakan untuk menarik perhatian dan membuat siswa aktif dalam proses pembelajaran. Penggunaan media pembelajaran yang belum maksimal membuat siswa kurang termotivasi dalam mengikuti pembelajaran, sehingga hasil belajar siswa rendah. Inovasi dalam pembelajaran PAI sangat dibutuhkan, guna meningkatkan motivasi dan hasil belajar siswa. Salah satu media pembelajaran tersebut yaitu dengan media pembelajaran autoplay media studio dan focusky. Tujuan dari penelitian ini adalah untuk menjelaskan perbedaan motivasi belajar dan hasil belajar siswa antara kelompok yang menggunakan media pembelajaran autoplay media studio, kelompok yang menggunakan media pembelajaran focusky dan kelompok yang menggunakan pembelajaran konvensional pada mata pelajaran Pendidikan Agama Islam kelas VII di Sekolah Menengah Pertama Nurul Islam Jember. Hasil analisis menunjukkan bahwa (1) ada perbedaan motivasi belajar siswa antara kelompok yang menggunakan media pembelajaran autoplay media studio, kelompok yang menggunakan media pembelajaran focusky dan kelompok yang menggunakan pembelajaran konvensional pada mata pelajaran Pendidikan Agama Islam Kelas VII di Sekolah Menengah Pertama Nurul Islam Jember dengan nilai F sebesar 3,606 dengan signifikansi 0,031. (2) ada perbedaan hasil belajar siswa antara kelompok yang menggunakan media pembelajaran autoplay media studio, kelompok yang menggunakan media pembelajaran focusky dan kelompok yang menggunakan pembelajaran konvensional pada mata pelajaran Pendidikan Agama Islam Kelas VII di Sekolah Menengah Pertama Nurul Islam Jember dengan nilai F sebesar 3,913 dengan signifikansi 0,024. (3) ada perbedaan motivasi belajar dan hasil belajar siswa antara kelompok yang menggunakan media pembelajaran autoplay media studio, kelompok yang menggunakan media pembelajaran focusky dan kelompok yang menggunakan pembelajaran konvensional pada mata pelajaran Pendidikan Agama Islam Kelas VII di Sekolah Menengah Pertama Nurul Islam Jember untuk Pillae Trace (sig. 0,010), Wilk Lambda (sig. 0,008), Hotelling Trace (sig. 0,007), Roy’s Largest Root (sig. 0,001). Artinya, untuk Pillae Trace, Wilk Lambda, Hotelling Trace, Roy’s Largest Root semuanya signifikan.